A comparative study of self-praise on English and Chinese social media: strategies, themes, and motivations - Wu, Hanwei; Zhang, Lehua; Ren, Shuai (Frontiers in Psychology, 2023)
The act of self-praise, a novel and prevalent discourse pattern on social media across different cultures, is still understudied. As such, this study delves into self-praise from linguistic and psychological perspectives by examining and comparing the strategies, themes, and motivations of self-praise on English and Chinese social media. A discourse-based analysis of the data comprising 200 posts from Twitter (English) users and 200 posts from Weibo (Chinese) users revealed that Twitter users favored more unmodified explicit self-praise strategies, while Weibo users opted for more implicit self-praise strategies. Both groups employed explicit self-praise equally, but with different sub-strategies. The most prevalent themes were appearance, competence/performance, skills, virtues, and self-encouragement. Appearance was more dominant among Twitter users, whereas skills and self-encouragement were more popular among Weibo users. Both groups valued competence/performance and virtues, but with different virtues. Twitter users valued cherishing friendship, bravery, and maturity, whereas Weibo users stressed kindness, cherishing kinship, and thoughtfulness. Two semi-structured interviews conducted with six Twitter participants and six Weibo participants indicated that the motivations for online self-praise in both groups were psychological needs such as self-flattery, self-presentation, and self-encouragement, while commercial profit was a motivation only for Weibo participants. This study also discusses the social and cultural factors that may account for these differences and provides implications for future research on online self-praise.